Edukasi Kesehatan Penyakit Stroke pada Usia Produktif melalui Diskusi Publik bersama Yastroki - Mogi, Amelia Haness; Novelia, Nina; Ganiem, Leila Mona (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Stroke is one of the leading causes of death and disability worldwide, including in Indonesia. This condition can affect anyone, including individuals in their productive years, due to risk factors such as hypertension, diabetes, obesity, and unhealthy lifestyles. The prevalence of stroke in Indonesia continues to rise, with an increasing number of cases occurring among people under the age of 50. Public discussion activity highlights the importance of Personal Social Responsibility (PSR) in raising public awareness about stroke, especially among people in their productive age. Collaboration between the fields of communication and medicine can produce more effective educational strategies by delivering information in a simpler and more understandable way. One of method is a public discussion titled "Be Great, Don’t Regret," involving approximately 100 (hundred) persons medical professionals, academics, organizations such as the Indonesian Stroke Foundation (Yastroki), and community groups in Jakarta, Indonesia. In the discussion which was held at LSPR Campus, it was interactive, focusing on the main theme of the importance of balancing achievement with physical and mental health. Additionally, there were sub-themes on early detection, stress management, and healthy lifestyle habits. The event concluded with a reflection session and the participants' personal commitments to adopting a healthy lifestyle.ABSTRAKStroke merupakan salah satu penyebab utama kematian dan disabilitas di dunia, termasuk di Indonesia. Penyakit ini dapat menyerang siapa saja, termasuk individu dalam usia produktif, akibat faktor risiko seperti hipertensi, diabetes, obesitas, serta gaya hidup tidak sehat. Prevalensi stroke di Indonesia terus meningkat, dengan kasus yang semakin banyak terjadi pada kelompok usia di bawah 50 tahun. Kegiatan diskusi publik ini menyoroti pentingnya masyarakat melakukan PSR (Personal Social Responsibility) dalam rangka meningkatkan kesadaran masyarakat tentang stroke, terutama bagi usia produktif. Kolaborasi antara ilmu komunikasi dan kedokteran dapat menghasilkan strategi edukasi yang lebih efektif, dengan penyampaian informasi yang lebih sederhana dan mudah dipahami. Salah satu metode yang dilakukan adalah diskusi publik bertajuk "Be Great, Don’t Regret", yang melibatkan kurang lebih 100 (seratus) orang tenaga medis, akademisi, organisasi seperti Yayasan Stroke Indonesia (Yastroki) dan komunitas di Jakarta, Indonesia. Dalam diskusi yang diselenggarakan di kampus LSPR ini, berlangsung interaktif, membahas tema besar tentang pentingnya keseimbangan antara prestasi dan kesehatan fisik dan mental. Selain itu, juga sub-tema mengenai deteksi dini, manajemen stres, dan pola hidup sehat. Hingga acara ditutup dengan sesi refleksi dan komitmen pribadi peserta untuk memulai gaya hidup sehat.